NILAI-NILAI RELIGIUS ISLAM DALAM ANTOLOGI CERPEN “CARAKU MENCINTAI KANG ALFI (ALFIYAH LATIN)” KARYA LIA HIMMATUL ULYA - Asngadi Rofiq; Moh. Syamsul Ma’arif (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
Literary works, especially short stories, are one of the teaching tools to develop the soul, humanize humans, and increase literary appreciation in depth and love, coloring short stories as a form of manifestation of life. As a form of literary work, the short story also tells about various human lives and their interactions with the environment and each other. One of the literary works in the form of short stories that really builds the soul and character of Indonesian children, one of which is a short story entitled "CARAKU MENCINTAI KANG ALFI (ALFIYAH LATIN)'' by Lia Himmatul Ulya. This short story genre is very different from other short stories. The author is very good at presenting the contents of this short story so that it is neat and touching when read. This short story also presents religious values related to God and between humans themselves. This anthology of short stories in addition to providing entertainment also instills religious values with familiar language so that it can be easily understood and implemented by readers in everyday life.The general purpose of this study is to examine Islamic religious values in the short story CARAKU MENCINTAI KANG ALFI (ALFIYAH LATIN) by Lia Himmatul Ulya, which is sourced from the Qur'an and Al-Hadith. The specific objectives of this study are (1) to obtain an objective description of religious values in relation to God (vertical) and (2) to obtain an objective description of religious values in relation to fellow human beings (horizontally). This study uses a qualitative approach, with the characteristics of (1) using a natural setting as a direct data source and as the main instrument, (2) descriptive, (3) paying more attention to the process than the result, (4) analyzing the data inductively and meaning. . This research is classified into descriptive qualitative research. The data in this study are the religious values of the short story text CARAKU MENCINTAI KANG ALFI (ALFIYAH LATIN).Based on the results of this descriptive research, it was found that the Islamic religious values contained in the short story CARAKU MENCINTAI KANG ALFI (ALFIYAH LATIN) include "Hablum minallah and Hablum minan-nas". In relation to God, seven religious values are found, namely: (1) the value of faith (2) the value of endeavor, (3) the value of tawakkal, (4) the value of patience, (5) the value of guidance, (6) the value of monotheism, (7 ) God's help, while in relation to fellow human beings three religious values are found, namely: (1) mutual help among human beings, (2) mutual respect and respect for fellow human beings, (3) tolerance between religious communities. From some of the religious values presented by the author in this short story, he voiced the concept of Islamic Aqeedah which can be used as a good role model for readers. Because the contents of this short story include many religious teachings sourced from the Qur'an and Al-Hadith. And from here also the author emphasizes the importance of human relationships with God and human relationships with fellow human beings.